APPLICATION OF THE SELIC RATE TO THE MONETARY UPDATE OF TAX UNDUE PAYMENTS (CIPEEX, 2025)
This paper examines the application of Brazil’s SELIC rate to the monetary update of tax undue payments, focusing on refunds and set-offs under federal law and superior court case law. It aims to define the scope of SELIC as a single index (interest plus inflation) in both refund of undue payments and the remuneration of judicial and extrajudicial deposits, and to assess the prohibition on cumulating SELIC with other indices. Methodologically, it combines a literature review, analysis of the relevant statutes (notably Laws Nos. 9,250/1995 and 9,703/1998), and a survey of precedents, emphasizing the ratio decidendi and practical consequences for taxpayers and the Treasury. The findings show a consolidated understanding that SELIC operates as the standard index for updating and remunerating taxpayers’ credits in the federal sphere, barring overlap with autonomous correction or interest and properly distinguishing deposit remuneration from the update of undue-payment credits. Practical effects include greater predictability and standardized calculations, with fewer disputes, subject to subnational specificities and administrative procedures. It concludes that adopting SELIC as a single index enhances legal certainty, prevents double counting (bis in idem), and promotes stability in taxpayer-tax authority relations.
Keywords: SELIC rate; tax undue payment; monetary update; refund and set-off